2017
DOI: 10.1021/acs.jafc.7b03953
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anti-Inflammatory Properties of Nobiletin in Macrophages by a Nano-Emulsion Preparation

Abstract: Lots of active substances are hydrophobic materials at ambient and body temperatures, decreasing their bioavailability and posing great challenges to successful incorporation into medication and functional foods. The goal of this research was to develop a nanoemulsion delivery system containing a hydrophobic crystalline bioactive component (nobiletin) to improve the anti-inflammatory activity. Nobiletin was incorporated into the oily phase, and the nanoemulsions were fabricated using high-speed and high-pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…In this study, we demonstrated the antileukemic effects of NOB at concentrations 10−100 µM in K562 cells, which were used in several anticancer studies in vitro, though it was higher than what can be achieved in vivo. Thus to increase the bioavailability and potent bioactivity of NOB in vivo, novel chemical modification, formulation or delivery system is needed to increase its solubility and reach the concentration we found in this study [45,46].…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we demonstrated the antileukemic effects of NOB at concentrations 10−100 µM in K562 cells, which were used in several anticancer studies in vitro, though it was higher than what can be achieved in vivo. Thus to increase the bioavailability and potent bioactivity of NOB in vivo, novel chemical modification, formulation or delivery system is needed to increase its solubility and reach the concentration we found in this study [45,46].…”
Section: Discussionmentioning
confidence: 87%
“…Western blot analysis was performed according to the previous method with slight modification (Liao et al., ). Briefly, each protein samples (20 µg/well) were resolved and electrophoresed by 10% SDS‐PAGE, and then were transferred onto nitrocellulose membranes (Millipore, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer, ovarian cancer, prostate cancer, colon cancer [148], liver cancer, hepatocellular carcinomas, glioblastoma, gastric cancer, lung cancer, nasopharyngeal cancer [149] Nano-emulsion [150], micelles…”
Section: Nobiletinmentioning
confidence: 99%